Inquiry - Based Learning - Sirry, Asmaa’ Mahmoud (Eximia, 2023)
Inquiry-based learning is a learning process that engages students by making real-world connections through exploration and high-level questioning. It is an approach to learning that encourages students to engage in problem-solving and experiential learning. In guided inquiry, the teacher further empowers student agency by providing several essential questions, having the students select the resources they will use to research their answers, and allowing them to choose how they will demonstrate understanding. Through inquiry, students engage in research around interesting ideas and fundamental questions. Questioning, critical thinking, and the creative development of new knowledge through inquiry are as important ( if not more so ) to learning as information finding through research.